Uma análise socioeconômica dos ingressantes do curso de Licenciatura em Química da Unesp/Ar durante o período de 1996 – 2018 - Junior, André Luis Pinotti [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Education has a extremely importance for Society and to understand it is necessary to know who are the people behind. So understand who are the educators is inherent to this process. Thus, this work aimed to make a socioeconomic analysis of students enrolled in the Chemestry graduation course at Unesp in Araraquara between the Years 1996 – 2018. To caracterize this analysis were realized graphics and the association Chi-Square test in order to correlate the variable (questions) with the group (year, presidential terms). This analysis was made about two questions present in Vunesp’s socioeconomic questionnaire. The first question analyzed was “Where did you go to High school?” (Question 9) and the second “What is your family’s total monthly income?” (Question 25). At the end of this work it was possible to notice that the association between the questions (9 and 25) and the presidential terms in fact happened and that with this correlation, it was possible to make a few notes that indicate that the brazilian campus during this studied period may have experienced its democratization.

A educação é de extrema importância para a sociedade e para entende-la é necessário saber quem são as pessoas por trás, dessa maneira entender quem são os docentes é inerente a esse processo. Dessa maneira, esse trabalho teve como objetivo fazer uma análise socioeconômica dos alunos inscritos do curso de Licenciatura em Química da Unesp de Araraquara entre 1996 e 2018. Para caracterizar essa análise foram realizados gráficos e o teste de Qui-Quadrado de associação de maneira a correlacionar a variável (questões) com o grupo (anos, mandatos presidenciais). Essa análise foi feita acerca de duas questões presentes no questionário socioeconômico da Vunesp. A primeira questão analisada foi “Onde você cursou o ensino médio?” (Questão 9) e a segunda “Qual a renda total mensal de sua família?” (Questão 25). Ao final desse trabalho foi possível perceber que a associação entre as questões (9 e 25) com os mandatos presidenciais de fato aconteceu e com essa correlação foi possível fazer alguns apontamentos que indicam que realmente o campus brasileiro ao longo desse período estudado pode ter vivenciado uma a democratização.
A socioeconomic analysis of newcomers to the Licentiate Degree in Chemistry at Unesp/Ar during the period 1996 – 2018
Keywords: Química; Perfil socioeconômico; Educação superior